2021
DOI: 10.1590/0034-7167-2020-0790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with acute kidney injury in patients in intensive care units

Abstract: Objectives: to identify the prevalence and factors associated with the development of acute kidney injury in critically ill patients. Methods: a cross-sectional study, conducted from June 2018 to August 2019. The Kidney Disease Improving Global Outcomes was used to classify acute kidney injury. A significant value was set at p<0.05. Results: a total of 212 patients were included, of whom 35.8% evolved into an acute kidney injury. Patients with acute kidney injury had hypertension, higher levels on severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Verificou-se relação entre óbito e pacientes internados em UTIs. Similarmente um estudo realizado no Nordeste brasileiro entre pacientes hospitalizados em UTI detectou que mais da metade dos pacientes com IRA foi a óbito (56,1%) [22]. Pacientes críticos internados em UTI apresentam quase 50% a mais de chance de desfecho fatal quando comparados a pacientes sem IRA [23,24].…”
Section: Resultsunclassified
“…Verificou-se relação entre óbito e pacientes internados em UTIs. Similarmente um estudo realizado no Nordeste brasileiro entre pacientes hospitalizados em UTI detectou que mais da metade dos pacientes com IRA foi a óbito (56,1%) [22]. Pacientes críticos internados em UTI apresentam quase 50% a mais de chance de desfecho fatal quando comparados a pacientes sem IRA [23,24].…”
Section: Resultsunclassified
“…
Fig. 1 Conceptual framework adapted after review of different literature on factors associated with AKI in COVID-19 patients [ 16 18 ]
…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Acute kidney injury (AKI), a very common complication of sepsis, is a sudden decrease in renal function within a short period caused by various etiologies [ 5 ]. Studies have shown that patients in the intensive care unit (ICU) are more likely to develop AKI due to clinical instability and previous risk factors, including advanced age, sepsis, hypovolemia, surgery, and nephrotoxic medication [ 6 , 7 ]. Up to 50% of AKI cases are associated with sepsis, and up to 60% of patients with sepsis develop AKI [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%